Concerning the Increase of Natural Population in the Lithuanian SSR - Merčaitis, Antanas (Problemos, 1968)
The paper investigates the natural movement of the Lithuanian population in the post-war years. On the basis of the study of the death rate dynamics of the population the conclusion has been drawn that at present and in the near future the birth rate will still be playing a great role in determining the level of the natural increase of the population in the Lithuanian SSR. The basic part of the paper is devoted to the analysis of the changes of the birth rate, and to how the woman’s social status, the level of the satisfaction of material and cultural needs, urbanisation and other factors affect the level of the birth rate. A conclusion is made that the present indexes of the natural population movement are still ensuring reproduction on a large scale although on a much smaller basis.